Parallel, multi-stage processing of colors, faces and shapes in macaque inferior temporal cortex - Lafer-Sousa, Rosa; Conway, Bevil R (Nature neuroscience, 2013)
The authors study fMRI responses to colors and achromatic images to address the fundamental organizational principles of monkey inferior temporal cortex. They report color-biased regions adjacent and ventral to face patches, at locations predicted by a series of coarse eccentricity maps. Visual-object processing culminates in inferior temporal cortex (IT). To assess the organization of IT, we measured functional magnetic resonance imaging responses in alert monkeys to achromatic images (faces, fruit, bodies and places) and colored gratings. IT contained multiple color-biased regions, which were typically ventral to face patches and yoked to them, spaced regularly at four locations predicted by known anatomy. Color and face selectivity increased for more anterior regions, indicative of a broad hierarchical arrangement. Responses to non-face shapes were found across IT, but were stronger outside color-biased regions and face patches, consistent with multiple parallel streams. IT also contained multiple coarse eccentricity maps: face patches overlapped central representations, color-biased regions spanned mid-peripheral representations and place-biased regions overlapped peripheral representations. These results show that IT comprises parallel, multi-stage processing networks subject to one organizing principle.